Reframing Islamic State: Trends and themes in contemporary messaging - Telli Betül Karacan (Danish Institute for International Studies (DIIS), 2020)
This report uses content analysis to identify and compare trends in Islamic State's contemporary messaging, their main internal debates and their priorities over a sixmonth period between October 2019 and April 2020. The study explores the nuances and dynamics of the organisation's world view and the extent to which external and internal setbacks have affected its cohesiveness and structure. It shows that the Islamic State movement has successfully mobilised itself after the military pushback against it and finds that the organisation perceives itself as undefeated. The analysis reveals a geographical shift in the attention of the Islamic State movement, prioritising activities in the West outside its core territory in Syria and Iraq. To explore one of their new geographical focus points, the report also focuses on South Asia. Finally, the organisation has increased and intensified its attacks, thus expanding its footprints and regaining lost territory. In sum, the organisation is in a phase of resurgence, as it is still a potent force with global tentacles, and there are no indications that it is being disrupted.
Keywords: 300; Islam; Krieg; Bürgerkrieg; Terrorismus